Impact of particulate matter exposure on forced vital capacity and respiratory symptoms in landfill workers - Febby Jazilatul, Hamidah; Dwinda Oktavia, Ariska; Akas Yekti Pulih, Asih; Kuuni Ulfah Naila, El Muna; Edza Aria, Wikurendra; Josfirin Uding, Rangga (Tehran University of Medical Sciences, Tehran, Iran, 2025)
Introduction: Exposure to particulate matter in the workplace has been identified as a major contributing factor to respiratory diseases including decreased lung function. In developing countries, health and safety of landfill workers receives little attention. Thus, it is necessary to conduct an in-depth investigation into particulate matter exposure and its link to disease. This study to investigate the relationship between exposure of Particulate Matter (PM2.5) on forced vital capacity and respiratory symptoms in landfill workers. Materials and methods: Measurements of PM2.5 parameter air samples were taken using an SNDWAY brand detector from five locations. Interviews using questionnaires with 49 landfill worker respondents were conducted to determine respiratory symptoms. Forced vital capacity was examined with a Voldyne 4000 incentive spirometer and the results were analyzed with chisquare statistical analysis. Results: The highest PM2.5 concentrations occurred during the day in the west, east, and center, which fall into the unhealthy category. Most of the respondents had abnormal forced vital capacity (32 people, 65.3%) and respiratory symptoms (43 respondents, 87.8%). Chi-square analysis showed a statistically significant association between PM2.5 exposure and abnormal FVC with a p-value of 0.002 and an Odds Ratio (OR) of 10.0 (95% CI: 2.41–41.58). Conclusion: This study found a significant association between PM2.5 exposure and abnormal Forced Vital Capacity (FVC) in landfill workers (p = 0.002; OR= 10.0; 95% CI: 2.41–41.58). These findings indicate that workers exposed toPM2.5 are at increased risk of lung function impairment, underscoring the need for routine respiratory health monitoring and targeted exposure mitigation in landfill environments.